Protein structural insights into a rare PCSK9 gain-of-function variant (R496W) causing familial hypercholesterolemia in a Saudi family: whole exome sequencing and computational analysis - Shaik, Noor Ahmad; Al-Shehri, Najla; Athar, Mohammad; Awan, Ahmed; Khalili, Mariam; Al Mahadi, Hadiah Bassam; Hejazy, Gehan; Saadah, Omar I.; Al-Harthi, Sameer Eida; Elango, Ramu; Banaganapalli, Babajan; Alefishat, Eman; et al. (Frontiers in Physiology, 2023)
Familial hypercholesterolemia (FH) is a globally under-diagnosed genetic condition associated with premature cardiovascular death. The genetic etiology of Arab FH patients is scarce. Therefore, this study aimed to identify the genetic basis of FH in a Saudi family using whole-exome sequencing (WES) and multidimensional bioinformatic analysis. Our WES findings revealed a rare heterozygous gain-of-function variant (R496W) in the exon 9 region of the PCSK9 gene as a causal factor for FH in this family. This variant was absent in healthy relatives of the proband and 200 healthy normolipidemic controls from Saudi Arabia. Furthermore, this variant has not been previously reported in various regional and global population genetic variant databases. Interestingly, this variant is classified as "likely pathogenic" (PP5) based on the variant interpretation guidelines of the American College of Medical Genetics (ACMG). Computational functional characterization suggested that this PCSK9 variant could destabilize the native protein and alter its secondary and tertiary structural features. In addition, this variant was predicted to negatively influence its ligand-binding ability with LDLR and Alirocumab antibody molecules. This rare PCSK9 (R496W) variant is likely to expand our understanding of the genetic basis of FH in Saudi Arabia. This study also provides computational structural insights into the genotype-protein phenotype relationship of PCSK9 pathogenic variants and contributes to the development of personalized medicine for FH patients in the future.